Analysis of the cone penetration test in layered clay - Walker, James; Yu, Hai-Sui (Thomas Telford (ICE Publishing), 2010)
This paper presents an analysis of the cone penetration test in multi-layered clays using the commercial finite-element code Abaqus/Explicit. The von Mises yield criterion and its associated flow rule are assumed to model the plastic behaviour of elastoplastic undrained clays. An arbitrary Lagrangian–Eulerian scheme and an enhanced hourglass algorithm are adopted to preserve the quality of mesh throughout the numerical simulation. Initially, the behaviour of the penetration resistance is examined in a soil with only two layers. The bottom layer is the weaker of the two and the behaviour of the penetration resistance when the cone approaches the lower layer is studied. The investigation is then extended to study the cone penetration test in a multi-layered clay by sandwiching a weaker clay layer between two stronger clay layers. The thickness of the weaker clay layer is varied and the behaviour of the penetration resistance is studied in relation to the thickness and relative strength of the soil layers. The results are discussed with respect to the soil mechanisms that are present when the cone moves past the relevant layer boundaries so that the position of these boundaries can be determined more accurately.